Environmental Justice, Ontological Turn and Queer Ecology: Toward a Futurity Free from Cis-Heterosexism - Guerrero Mc Manus, Siobhan (2026)
This essay establishes a dialogue between three contemporary analytical frameworks: intergenerational environmental justice, the ontological turn in anthropology, and queer ecology. Its aim is to contribute to the development of a notion of intergenerational environmental justice that breaks with the inertia of the Western liberal tradition and its humanist legacy, characterized by individualistic, presentist, and anthropocentric biases. These biases have hindered the inclusion of non-human entities and future generations within the normative horizon of justice. In response, the essay proposes recovering non-Western traditional worldviews, whose communal and relational ontologies offer epistemic and ethical alternatives for addressing the contemporary ecosocial crisis. However, it also warns that these ontologies can reproduce forms of cis-heteronormativity, and thus argues for the integration of the critical tools offered by queer ecology in order to build justice proposals that are truly inclusive, decolonial, and emancipatory.